Nitrogen, phosphorous and potassium polymeric microparticles: Application and validation of analytical methods for determination of a promising fertilizer - Chagas, Júnior Olair; Gomes, José Messias; Valadares Rodrigues, Júlia Helena; De Matos Cunha, Isabela Cristina; De Melo, Nathalie Ferreira Silva [UNESP]; Da Silva, Gilmare Antônia; Lobo, Fabiana Aparecida (My University, 2021)
Traditional analytical methods were applied to microparticles synthesized using a mixture of polymers. The microparticles containing nitrogen, phosphorus and potassium (NPK) were developed for application as a controlled release alternative to traditional fertilizers. Thus, analytical methods for the evaluation of nitrogen, phosphorus and potassium (essential nutrients for plants) in polymeric microparticles were applied and the results validated for this kind of sample. The linearity of the methods was established in the range of 10 to 20 mg L-1 for N, 0 to 2 mg L-1 for P and 0 to 2.4 mg L-1 for K. The relative standard deviation (RSD) of intermediate precision of the method was < 1% and recoveries from 99 to 108% for all nutrients were reached. The method proved to be selective, linear, precise and accurate for quantifying NPK in polymeric microparticles. In this way, it was possible to evaluate the correct nutrient encapsulation capacity in the synthetized polymeric microparticles, which is of fundamental importance since this will directly interfere in the success of the intended fertilization process.
Keywords: Encapsulated fertilizers; Flame atomic absorption spectroscopy; Kjeldahl method; Polymeric microparticles; Stannous chloride method